Pola Pewarisan Berkelanjutan Rumah Tradisional Jawa Di Desa Wisata Brayut - Setiadi, Dias Oktri Raka; Baiquni, Muhammad (Universitas Diponegoro, Indonesia, 2020)
Brayut is the only tourism village in Sleman Regency which has a traditional settlement that is still maintained. The existence of traditional houses as a tourist attraction in the Brayut Tourism Village plays a role in shaping the pattern of settlements in the present. This study intends to identify sustainable patterns of inheritance of traditional Javanese houses in the Brayut Tourism Village. The case study research method is the saturated sample (census) technique of 24 traditional Javanese homeowner households. The pattern of inheritance of traditional Javanese houses in the Brayut Tourism Village refers to the existence of institutions (customs, government regulations) and assets (human, natural, physical, social, financial). These aspects are flexible and not absolute so that they can adjust the livelihood conditions in each household. There are 5 patterns of home inheritance namely patrilineal, adaptation, major, patrilineal collective, and not yet inherited. The principle of preservation of the house as an ancestral heritage is still maintained, especially after the existence of a tourist village and government attention to several houses by establishing it as a cultural heritage building that gets expert assistance and maintenance funds.